Geochronological insights of middle miocene primates and vertebrate fauna of Ramnagar (J&K, India): Integrating litho- and magnetostratigraphy - Deepak Choudhary; Christopher C. Gilbert; Christopher J. Campisano; Daniel J. Peppe; Mohammad Arif; Sarvendra Pratap Singh; Kahsay Tesfay; Biren A. Patel; Wasim Abass Wazir; Rohit Kumar; Binita Phartiyal; Ningthoujam Premjit Singh; et al. (PLoS ONE, 2026)
The Middle Miocene site of Ramnagar (Jammu and Kashmir), India is well-known for its fossil primates including Sivapithecus indicus, Kapi ramnagarensis, and Ramadapis sahnii . Although always suggested as similar in age to the Chinji Formation of the Potwar Plateau, Pakistan, no precise geochronological age estimates of Ramnagar have yet been obtained. Furthermore, despite some notable previous efforts, the stratigraphic section in the Ramnagar region has not been satisfactorily documented. Therefore, it has long been unclear exactly how the fossil localities around Ramnagar relate to each other or to other Middle Miocene Siwalik localities stratigraphically or chronologically. Here we present new paleomagnetic and revised stratigraphic data for most of the Ramnagar primate-yielding localities. Additionally, we document a near-complete chronology of all the mammal yielding sites belonging to the main ~440 m thick section of the Lower Siwaliks at Ramnagar. We anchor the paleomagnetic results using existing rodent-based biochronology, and further extrapolate ages using sediment accumulation rates to help constrain possible correlations to the Geomagnetic Polarity Time Scale (GPTS). Our preferred interpretation constrains all the primate yielding sites from Ramnagar to between ~13.03 Ma and ~11.59 Ma. Moreover, the first appearance datum (FAD) of the stem hylobatid Kapi ramnagarensis and sivaladapid Ramadapis sahnii can now be placed between 12.88–13.03 Ma (incorporating two possible correlations). Further, the FAD of the great ape Sivapithecus can be pushed back into this same time range as well, thereby extending its known chronological range by up to 200,000 years.